55 The impact of emotional disclosure as a form of therapeutic intervention on health-related outcomes and on the well-being of people with advanced disease: a systematic review. Issue 3 (1st September 2017) - Kupeli, Nuriye; Chatzitheodorou, Georgia; Candy, Bridget
Abstract : Introduction: Therapeutic emotional disclosure has been associated with positive psychological, physiological and behavioural changes. 1 In the form of expressive writing it commonly involves writing about a traumatic experience for 15 min over 3–5 consecutive days. 2 There is evidence that expressive writing in people with cancer may reduce pain and improve energy levels, sleep and psychological symptoms. 3 It has not been established in a review whether these interventions benefit people with advanced disease. Aims: To critique and pool the evidence from randomised controlled trials (RCTs) and other comparative studies on the effectiveness of emotional disclosure in adults with advanced disease and to explore the text analysis of participant's emotional disclosure. Method: Four databases (Pubmed, CENTRAL, CINAHL, PsycINFO), conference proceedings and a trials register were searched for relevant studies in March 2017. A combination of MeSH and free-text terms on emotional disclosure and end-of-life were used. Key review processes will be undertaken in duplicate. If appropriate meta-analysis will be considered. Results: The search identified unique 9014 citations. Screening these identified 33 potential relevant studies. Following full text review and contact with authors to clarify their sample population, nine studies on expressive writing met our inclusion criteria. Six were RCTs and three provide text analysis of emotional disclosure responses. Conclusion: This review is at data extraction phase, it will be completed (as part of an Msc) by September. The findings will provide best evidence on whether a relatively simple intervention can help improve the wellbeing of people with advanced disease. References: . Pennebaker, J.W., 1997. Writing about emotional experiences as a therapeutic process. Psychological Science, 8(3), pp.162–166. . Pennebaker, J.W. and Beall, S.K., 1986. Confronting a traumatic event: toward an understanding of inhibition and disease. Journal of Abnormal Psychology, 95(3), p.274. . Merz, E.L., Fox, R.S. and Malcarne, V.L., 2014. Expressive writing interventions in cancer patients: a systematic review. Health Psychology Review, 8(3), pp.339–361.